The Role of Artificial Intelligence Powered Drones In Strengthening Counter-Banditry Operations in North West Nigeria - Ayoola Olayiwola Richard; Aisha Ajoke Abdussalam; Praise Fisayo Duyile (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2026)
The rapid pace of technological advancement has led to more complex warfare, with uncrewed aerial vehicles (UAVs), commonly known as drones, becoming central to military operations worldwide. The paper assesses the impact of AI-powered drones on improving counter-banditry efforts in North-West Nigeria. In this region, armed banditry has severely affected security and socio-economic stability. Using Network-Centric Warfare (NCW) Theory as its theoretical basis, the study explores how AI-driven unmanned aerial systems (UAS) can enhance real-time intelligence, surveillance, and reconnaissance (ISR), thereby facilitating quicker decision-making and better-coordinated actions among Nigerian security personnel. The paper employed a qualitative methodology, examining secondary data from journal articles, government documents, military publications, newspapers, and case studies on the use of AI and drones in conflict areas. The findings indicate that AI-enhanced drones can greatly improve target identification, predictive analytics, and rapid response capabilities, ultimately bolstering Nigeria’s counter-banditry initiatives in the North West of Nigeria. The study concludes with policy suggestions for incorporating AI-driven drone technology into Nigeria’s security framework while addressing ethical and legal issues.